Telephone-based re-education on the day before colonoscopy improves the quality of bowel preparation and the polyp detection rate: a prospective, colonoscopist-blinded, randomised, controlled study. Issue 1 (16th March 2013) - Liu, Xiaodong; Luo, Hui; Zhang, Lin; Leung, Felix W; Liu, Zhiguo; Wang, Xiangping; Huang, Rui; Hui, Na; Wu, Kaichun; Fan, Daiming; Pan, Yanglin; Guo, Xuegang
Abstract : Background: Despite advances in bowel preparation methods, the quality of bowel preparation in some patients undergoing colonoscopy remains unsatisfactory. The effect of telephone re-education (TRE) on the day before colonoscopy on the quality of bowel preparation and other outcome measures had not been studied. Methods: A prospective colonoscopist-blinded study was conducted. All patients received regular instructions during a visit to discuss colonoscopy. Those scheduled for colonoscopy were randomly assigned to receive TRE on the day before colonoscopy (TRE group) for bowel preparation or no TRE (control group). The primary outcome was the rate of adequate bowel preparation. The secondary outcomes included polyp detection rate (PDR), non-compliance with instructions, and willingness to repeat bowel preparation. Results: A total of 605 patients were randomised, 305 to the TRE group and 300 to the control group. In an intention-to-treat analysis of the primary outcome, adequate preparation was found in 81.6% vs 70.3% of TRE and control patients, respectively (p=0.001). PDR was 38.0% vs 24.7% in the TRE and control group, respectively (p<0.001). Among patients with successful colonoscopy, the Ottawa scores were 3.0±2.3 in the TRE group and 4.9±3.2 in the control group (p<0.001). Fewer patients who showed non-compliance with instructions were found in the TRE group (9.4% vs 32.6%, p<0.001). No significant differences were observed between the two groups with regard to willingness to have a repeat bowel preparation (p=0.409). Conclusions: TRE about the details of bowel preparation on the day before colonoscopy significantly improved the quality of bowel preparation and PDR.